Aspects Regarding the Use of Coco Model for Public Entities Internal Control - Madalina Beldiman (Risk in Contemporary Economy, 2016)
Control, from the semantic analysis point of view, is a permanent or regular activity, a situation, to track the overall progress and improvement measures. According to the Romanian legislation, internal control is defined as all forms of control exercised at the level of the public entity, including internal audit, established by management in accordance with its objectives and legal regulations, to ensure the management of public funds economically, efficiently and effective. In general, the audit includes organizational structures, methods and procedures.